Transmission of Real-time Video Signal with Interference Density and Human Traffic - Rizal Broer Bahaweres; Oki Teguh Karya; Mudrik Alaydrus (Universitas Ahmad Dahlan, 2015)
The use of mobile phone as a communication tool so rapidly increase, as well as various types of functions therein. Among of the many applications on the mobile phone, which are used skype android-based for teleconferencing via mobile phone. Things can not be separated from these applications is the need of qualified internet network access for these applications can be felt up function. One of the network access to the Internet is widely used today's society is a wi-fi network. Access to the Internet does not always provide the best performance, this is due to many factors, one of which is the presence of interference. In this study, we tested transmission of video signals in real-time using an application skype on the mobile phone. Skype run on wi-fi network, which is influenced by the presence of interference or objects such as human traffic in the network. Wireshark were used to obtain data reliability wi-fi network, known as QoS. While evalvid used to obtain the data QoE restricted only get the data PSNR (Peak Signal To Noise Ratio) and MSE (Mean Square Error).